Design of gasoline vapor ejection condensator from vapor and gas mixtures - Кологривов, Михаил Михайлович; Бузовский, Виталий Петрович (Eastern-European Journal of Enterprise Technologies, 2015)
The calculation method of the ejection apparatus, which operates with flammable and explosive vapor-gas flow is considered. Calculation of the apparatus is performed without prior experimental research of the operation with gasoline vapor. The calculation method is based on two models. The first Pazhi-Galustov model is theoretical, the second Andreev model uses similarity criteria. The Stefan formula, as applied to the polar coordinate system was derived, which has allowed to give a more rigorous description of the mass transfer mechanisms at the droplet interface. The results of Andreev E.I., obtained for the nozzle chambers of air conditioners were used for deriving the heat-mass transfer intensity equation according to the first model by numerical simulation. The approach, which has allowed to develop recommendations for a constructive design of the ejection apparatus for condensing gasoline vapors without dangerous experimental research was proposed. In particular, the numerical experiment has shown that in order to reduce materials consumption, the length of the apparatus is advisable to be no more than 1.5 m, and the ratio of mass flows of brine and vapor-gas mixture, providing the necessary gasoline vapor recovery degree must be at least 5:1.